TEACHER PROFESSIONAL DEVELOPMENT FOR INCLUSIVE EDUCATION: A MIXED-METHODS STUDY ON CO-TEACHING STRATEGIES FOR STUDENTS WITH DYSLEXIA - Mantas Petrauskas; Egle Kazlauskaite; Tomas Jankauskas (International Journal of Educatio Elementaria and Psychologia, 2025)
Inclusive education is increasingly recognized as a crucial approach to ensuring that all students, including those with disabilities like dyslexia, have access to quality education. However, effective implementation of inclusive education requires teachers to be adequately trained in strategies that support diverse learners. This study investigates the impact of teacher professional development (PD) programs focused on co-teaching strategies for students with dyslexia. The research aims to evaluate how PD programs improve teachers’ ability to implement co-teaching techniques and enhance the learning outcomes of students with dyslexia. Using a mixed-methods approach, this study combines quantitative data from pre- and post-intervention assessments on teachers’ knowledge and confidence in using co-teaching strategies, along with qualitative data from interviews and classroom observations. The results show a significant improvement in teachers’ understanding and implementation of co-teaching strategies, with students exhibiting improved engagement and academic performance in reading and writing tasks. Additionally, teachers reported increased confidence in addressing the needs of students with dyslexia in inclusive classrooms. The study concludes that targeted PD programs on co-teaching strategies can be a key factor in supporting inclusive education practices and improving outcomes for students with dyslexia. These findings underscore the importance of continuous professional development for teachers in fostering inclusive and equitable learning environments.